2018
DOI: 10.1108/cg-01-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Financial decisions and ownership structure as control mechanisms of agency problems: evidence from Italy

Abstract: Purpose The purpose of this study is to investigate the relationship between financial decisions and ownership structure by using the control contests on a sample of Italian listed companies. Design/methodology/approach The analysis adopts a balanced panel data set of 984 firm-year observations for the period of 2002-2013, with estimation using a generalized method of moments. Findings The results appear to confirm both the hypotheses of the alignment of interests and the entrenchment effect. The entrenchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 105 publications
(228 reference statements)
0
13
0
2
Order By: Relevance
“…In emerging markets, such as Qatar, concentrated ownership, family controlled/owned firms and ruling/royal family shareholdings and membership on the board of directors are common in listed firms. This unique situation can lead to different types of agency problems because of the conflicts of interest between: owners and lenders; owners and managers; majority and minority shareholders; and powerful directors that exercise “self-control” for their personal advantage (Schulze et al , 2001; Chrisman et al , 2004; Miller and Breton-Miller, 2006; Hassan, 2018; Rossi et al , 2018). …”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In emerging markets, such as Qatar, concentrated ownership, family controlled/owned firms and ruling/royal family shareholdings and membership on the board of directors are common in listed firms. This unique situation can lead to different types of agency problems because of the conflicts of interest between: owners and lenders; owners and managers; majority and minority shareholders; and powerful directors that exercise “self-control” for their personal advantage (Schulze et al , 2001; Chrisman et al , 2004; Miller and Breton-Miller, 2006; Hassan, 2018; Rossi et al , 2018). …”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…powerful directors that exercise “self-control” for their personal advantage (Schulze et al , 2001; Chrisman et al , 2004; Miller and Breton-Miller, 2006; Hassan, 2018; Rossi et al , 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In this line, Pindado and de la Torre (2008) state that dividends positively influence the level of shareholder concentration in Spanish companies, in which the significant shareholders are generally other companies. Rossi et al (2018) identify a U-shaped association amid dividends and concentration of ownership. In turn, Jensen (1986) states that managers use free cash-flows to benefit instead of distributing them as dividends because of ownership dispersion.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Jensen (1986) opined that in the absence of concentrated ownership, executives might expropriate free cash flow as their perks instead of distributing it as a dividend. Rossi et al (2018) found a U shaped relationship between dividend and ownership concentration.…”
Section: Determinants Of Ownership Concentrationmentioning
confidence: 97%